Angry and Afraid: Exploring the Impact of Mixed Emotional Reactions to Hate Crimes With LGBT+ and Muslim Communities - Paterson, Jenny (Journal of interpersonal violence, 2025)
Hate crimes send messages of intolerance that can cause significant emotional and behavioral harm to entire identity groups. Previous research, based on intergroup emotions theory, has helped explain the psychological mechanisms that underpin the indirect effects of anti-LGBT+ hate crime, showing that incidents give rise to perceptions of threat among community members, which in turn elicit certain emotional reactions that trigger specific behavioral outcomes. This article provides two significant contributions to this developing knowledgebase. First, it provides an important replication of the theoretical model with another frequently targeted community: Muslim people. In addition, it offers the first quantitative analysis of how combinations of different emotions trigger discrete behavioral responses in the aftermath of hate crime, thereby providing much-needed nuance to the intergroup emotions theory model. Across two studies (Study 1: N = 589 LGBT+ participants; Study 2: N = 347 Muslim participants), we show that, for both LGBT+ and Muslim participants, indirect experiences of hate crimes are associated with greater perceptions of threat, which are then positively associated with anger, anxiety, and shame, that link to behavioral intentions: avoidance, pro-action, security behaviors, and retaliation. Latent class analyses further revealed that participants’ emotional reactions tend to cluster into four distinct profiles in both communities: people scored mid-range on all emotions, or high anger with low shame, or high anger with high anxiety, or low shame. These combinations had direct implications for intended behaviors across both groups: experiencing high anger with high anxiety was a cogent motivator of action. Most significantly, we provide new insights into how and why different emotions interact to predict both similar and divergent behaviors in the aftermath of hate crime incidents. Our findings yield important new knowledge that holds the potential of shaping both public policies and practices aimed at addressing the impacts of hate crimes.